Design of Smart Robot Prototype Automatic Garbage Disposal Based on Arduino at Mega - Badriah Nursakinah (International Journal of Integrative Sciences, 2023)
The purpose of this research is to design a prototype for an automatic waste disposal robot based on Arduino AT Mega. The background of this research is rapid pace of technology in the era of digitalization where Artificial Intelligence is a field of science that is currently of great interest to many people, especially in the digital generation. The thing that we need to know is many human job almost replaced by automated machines or robotic technology. Nowadays, robots are used to make human work easier, such as throwing away piles of rubbish to the main waste disposer. This prototype of smart automatic waste disposal robot was designed and created as a human aid in the field of cleaning. The input process is carried out as an integration process between Arduino,  HCSR 04 sensor, and Infra Red Line Tracking sensor. For create Arduino, HCSR 04, and Line Tracking sensors can work optimally, the main thing is carry out the configuration process using a board and jumper cables as well as LED lights to ensure whether the sensors and other supporting tools are integrated with the Arduino